Study of the Most Important Influential Factors in the Selection and Purchase Decision Process of Women Cosmetic Products (Skin Cares) in North of Cyprus - Soosan, Aezoo (Eastern Mediterranean University EMU, 2015)
Marketers in cosmetics industry are required more perfect perception about consumer‟s behavior as a basis for making better strategic decisions regarding definition of market and production line as well as more appropriate tactic decisions concerning to taking the certain hybrid marketing measures. This study aims at searching for what kind of factors affect the buyers‟ behavior. The purpose was to compare the similarities and differences in two factors (internal and external). The descriptive data analysis at first phase included tables, diagrams, and charts used for organizing, summary, description, and raw data. The descriptive analysis measures the central tendency like mean, and median. To create a model, we should present approximation and or conjecture about the values and variables and their ratios with each other. The regression have been done between Depend variable and independent variable. The value of Cronbach alpha coefficient was 0.902 in this study, the result showed that before marketing managers should respond to problem recognition generated by outside factors, they must be able to identify consumer problems, because internal and external factors effects on consumer behavior. Keywords: External factors, Internal factors, Buying decision process, Cosmetic products

ÖZ: Pazarlama faaliyetlerini yürüten yöneticiler stratejik kararlar verirken tüketici davranışı ve algıları konusunda bilgi sahibi olmaları gerekmektedir. Ayrıca, pazarlama konusunda karar veren yöneticiler mevcut pazarın tanımı, üretim ile ilgili taktik kararlarda hybrid (karma) pazarlama ölçütlerini bilmek durumundadırlar. Çalışmanın temel amaçlarından birisi de tüketici davranışını etkileyebilecek etkenleri araştırmak ve içsel – dışsal faktörleri karşılaştırıp farklılık ve benzerlikleri ortaya çıkarmaktır. Çalışmanın ilk kısmında tanımsal veri analizlerine yer verilmiş ve toplanan verileri tanımlayan tablolar, şekiller, tanım ve ham veriler sunulmuştur. Tanımsal statistiklerde aritmetik ortalama ve medyan verilmiştir. Tüketicilerin davranışını açıklayıcı modelin ve ortaya konulan hipotezlerin test edilebilmesi amacı ile regresyon analizi yapılmıştır. Regresyon analizinde ise bağımlı ve bağımsız değişkenler arasındaki ilişki incelenmiştir. Kullanılan soruların geçerliliği güvenilirlik testi ile ölçülmüş ve 0.902 oranı ile örneğimizin güvenilir bir örnek olduğu saptanmıştır. Araştırma bulguları pazarlama konusunda karar verenlerin ilk önce dışsal faktörleri göz önüne almaları ortaya çıkmıştır. Anahtar Kelimeler: Dışsal faktörler, İçsel faktörler, Tüketici karar süreci, kozmetik ürünler
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2015. Supervisor: Assoc. Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Marketing Management; Marketing-Cosmetic Industry (Women Cosmetic Products)-Cyprus, North; Brand choice-Consumers' preferences; Consumers-Decision making-Shopping-Decision making; Consumer Behavior; External factors; Internal factors; Buying decision process; Cosmetic products